2006
DOI: 10.1111/j.1447-0578.2006.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Assisted hatching using a 1.48‐µm diode laser: Evaluation of zona opening and zona thinning techniques in human embryos

Abstract: We assessed the effectiveness of assisted hatching using a 1.48-µm diode laser in human embryos, comparing zona opening and zona thinning techniques. A total of 56 day 3 embryos were assigned randomly to a zona opening group, a zona thinning group, or a control group. We then carried out assisted hatching using the OCTAX Laser Shot system (MTG Medical Technology, Altdorf, Germany) in the first two groups. In the zona opening group, the inner membrane of the zona pellucida was broken to create a full-thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In line with previous findings involving mouse embryos and human embryos, we found that all three ZP manipulations significantly advanced the initiation of embryo hatching at E4.5, with a highest proportion of embryos hatching found in the ZP drilling group (14,17,18,20,21,(49)(50)(51). In addition, the reduced number of cells in hatching embryos from the ZP drilling group supported the fact that the artificially induced ZP opening allows embryos to begin hatching without reaching a certain embryonic cell number; this observation concurred with previous studies (20,31).…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous findings involving mouse embryos and human embryos, we found that all three ZP manipulations significantly advanced the initiation of embryo hatching at E4.5, with a highest proportion of embryos hatching found in the ZP drilling group (14,17,18,20,21,(49)(50)(51). In addition, the reduced number of cells in hatching embryos from the ZP drilling group supported the fact that the artificially induced ZP opening allows embryos to begin hatching without reaching a certain embryonic cell number; this observation concurred with previous studies (20,31).…”
Section: Discussionsupporting
confidence: 92%
“…The other studies, however, concluded that LAH on multiple-cell stage embryos failed to improve blastocyst formation and clinical pregnancy rate [25,26]. Wong et al reported that 114 donated blastomere stage embryos were divided into three groups: complete LAH, partial LAH and N-LAH.…”
Section: Kaartinen Et Al Summarized the Cumulative Live Birthmentioning
confidence: 99%
“…29 Nakagata et al, 30 Kawase et al 31 and Kaneko et al 32 reported that the problem of low fertility of C57BL/6 sperm caused by freezing damage is overcome by partially dissecting the zona pellucida, which also improves the fertility of sperm from subfertile transgenic mice, 33 and helps human IVF embryos at the blastocyst stage to hatch effectively. 34 In conclusion, we have shown that to preserve the fertility of mouse sperm from some inbred and hybrid mice at a high level, maltose, melezitose and raffinose are the best protectants to use in cryopreservation.…”
Section: Discussionmentioning
confidence: 82%
“…and Kaneko et al 32 . reported that the problem of low fertility of C57BL/6 sperm caused by freezing damage is overcome by partially dissecting the zona pellucida, which also improves the fertility of sperm from subfertile transgenic mice, 33 and helps human IVF embryos at the blastocyst stage to hatch effectively 34 …”
Section: Discussionmentioning
confidence: 99%